Implementasi Penataan Ruang di Kawasan Dataran Tinggi Dieng Kabupaten Banjarnegara - Vina Fadhrotul Mukaromah; Joni Purwo Handoyo (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2019)
Dieng Plateau is located across 6 administratives jurisdiction. It lays on 6 regencies, namely Banjarnegara, Wonosobo, Pekalongan, Batang, Temanggung, and Kendal. Most of priority part located in Banjarnegara. This research aims to analyze the condition of existing land use and its spatial planning. It also analyzes the suitability in both condition, based on criteria proposed by Ministry Regulation of ATR/BPN Number 6 Year 2017. Also, the factor causing this suitability. The method used is qualitative method. The existing condition is identified through Quickbird interpretation and field survey. Other primary and secondary data also collected from local government and population. This reseach shows that there are 11 existing land use that could be identified with the biggest amount of vegetable garden. For the planning, there are 10 types with the biggest amount of horticulture land. The level of suitability could be classified as high. From the criteria of type and amount, the unsuitability percentage is only 9,36%. While from the effect, the land use implementation effecting both local and regional scale. This condition is caused by natural factor, social factor, and other factor (technical factor and regulation factor). Key words : land use, spatial planning, spatial implementation